2020
DOI: 10.1128/mbio.02451-20
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Peptides Based on Human Angiotensin-Converting Enzyme 2 (ACE2) Potently Inhibit SARS-CoV-2 Infection In Vitro

Abstract: SARS-CoV-2 uses human angiotensin-converting enzyme 2 (ACE2) as the primary receptor to enter host cells and initiate the infection. The critical binding region of ACE2 is an ∼30-amino-acid (aa)-long helix. Here, we report the design of four stapled peptides based on the ACE2 helix, which is expected to bind to SARS-CoV-2 and prevent the binding of the virus to the ACE2 receptor and disrupt the infection. All stapled peptides showed high helical contents (50 to 94% helicity). In contrast, the linear control pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 37 publications
6
79
0
Order By: Relevance
“…There have been several reports based on the linear peptide fragment of the ACE2 PD α1 helix [13,23] Both biophysical and pseudoviral techniques have been used to assess the binding and activity, revealing that the peptides showed micromolar affinity and anti-viral activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports based on the linear peptide fragment of the ACE2 PD α1 helix [13,23] Both biophysical and pseudoviral techniques have been used to assess the binding and activity, revealing that the peptides showed micromolar affinity and anti-viral activity.…”
Section: Resultsmentioning
confidence: 99%
“…While preparing this manuscript, Curreli et al reported the design and synthesis of double stapled peptide analogues also based on native ACE2 PD α1. [23] We also synthesized double stapled analogues of the α1 helix, however these were isolated as crude mixtures of cis/trans alkene isomers and when tested in the pseudovirus inhibition assay and they showed no anti-viral activity (data not shown). In their studies, like us, they confirmed that the peptide designed by G. Zhang et al did not show any binding.…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral activity and superior α-helicity observed in the experimental study of Curreli et al 40 (which possess a double-stapled) might be partly understood by the results of our MD simulation study. According to Figure 4 , in which the initial and final structures from the MD studies of the control peptide and modification 15 are superimposed, the second stapled at the right side of the designed peptide helps to sustain this part of the structure in place in the complex with the S protein.…”
Section: Results and Discussionmentioning
confidence: 51%
“…This sequence was altered according to the proposed modifications (see Figure S1 (SI) for more details regarding the structures of all of the proposed peptides) followed by structure energy minimization in all positions where modifications were assigned (as described before for the receptor). Additionally, for comparison purposes, the best hydrocarbon stapled peptide based on the hACE2 helix published by Curreli and co-workers, 40 peptide NYBSP-4, was also modeled using the same protocol employed with the designed peptides. The NYBSP-4 peptide was also docked and underwent MD simulations using the same approaches described below.…”
Section: Methodsmentioning
confidence: 99%
“…Their data show that peptide fragments (P8, P9, P10) from the α-helix of the ACE2 peptidase domain (PD) that are rationally modified with residues that have a propensity for helical folding show high binding affinity and antiviral activity against authentic SARS-CoV-2 in the nanomolar range [118]. A study by Curreli et al also showed that peptides from a similar region of ACE2 that are structurally stabilized with double stapling show inhibitory activity against pseudotyped and live SARS-CoV-2 in the low micromolar range [119]. For peptides that are based on the binding motif of S1 RBD, particularly the RBM as shown in Fig.…”
Section: S1 and S2 Targeted Peptidesmentioning
confidence: 99%